Sensing the quantized reactivity of graphene - Lopes, Laís C. [UNESP] (2021)
We demonstrated that the variations measured in the quantum capacitance of single-layer graphene, envisioned here as a conceptual molecular model, depend on the chemical reactivity of the molecule and can be used as an analytical and sensing tool for environmental conditions. The variations are quantized as a function of the environmental changes and can be correlated with chemical reactivity indexes such as chemical hardness and softness. This not only constitutes a proof-of-principle that the chemical reactivity of graphene, as a single molecule, can be determined in situ by measuring the quantum capacitance, but also that these measurements can be used as an analytical tool.